INDONESIAN SMART SUKUK MODEL: OPPORTUNITIES AND CHALLENGES - Hudaya, Nurul; Hidayati, Ulfa Amani (STIT Sunan Giri Bima, 2024)
Micro, Small and Medium Enterprises (MSMEs) have long been the backbone of the Indonesian economy. Recent research shows that Sukuk can be a financing solution for MSMEs. However, the cost of Sukuk is higher than bonds in general, thus burdening MSMEs as issuers. The issue of issuance costs can be fixed through blockchain-based smart contract technology called smart Sukuk. This study aims to describe smart Sukuk's opportunities and the challenges it faces in its implementation in Indonesia. Several research has been done discussing Smart Sukuk and the general challenges of issuing Sukuk on the blockchain. This research focuses on the opportunities and challenges of issuing smart Sukuk and its implementation in Indonesia. The approach used in this study is a qualitative research method with a literature study. The findings show that several factors support the potential of smart Sukuk instruments in Indonesia, namely increased internet penetration, the Muslim population, an increase in young investors and a large number of MSMEs and their contribution to Indonesia's Gross Domestic Product. At the same time, the challenges in developing this evolutionary technology in Indonesia are the underlying regulations that have yet to be formed, unclear tax treatment, the tenor of Sukuk, liquidity risk, and cyber risk that are not evenly distributed.